Restricted Replication of Vesicular Stomatitis Virus in Human Lymphoblastoid Cells - Nowakowski, Maja (1973)
Replication of vesicular stomatitis virus (VSV) is restricted in one human lymphoblastoid cell line (Raji), but not in another similar cell line (Wil-2), compared with growth in HeLa cells. This restriction is characterized by a low proportion of cells yielding infectious virus and is associated with limited production of 42S virion RNA. Primary transcription of 13S and 26S VSV-specific RNA is not restricted in Raji cells, and the 13S RNA produced contains adenylate-rich sequences. This suggests that the block in Raji cells involves some step required for the replication of virion RNA.